PEMETAAN STATUS HARA KALIUM PADA TANAH SAWAH DI KECAMATAN BALINGGI, KABUPATEN PARIGI MOUTONG,PROVINSI SULAWESI TENGAH - Rudi Ariawan,Abdul Rahim Thaha,Sri Wahidah Prahastuti, I Made (AGROTEKBIS, 2016)
The aim of this research was to mapping the status of total and available potassium of lowland paddy soil in Balinggi Sub District, Parigi Moutong Regency, Central Sulawesi Province. The determination of locations where soils were sampled used a Global Position System (GPS) tool. The research was conducted from February to March 2015 and the soil samples were analyzed in Soil Science Laboratory of Agriculture Faculty Tadulako University. The results showed that the status of available potassium was low ranging from 0.15 cmol(+)kg-1 to 0.39 cmol(+)kg-1, whereas that of total potassium was varied from high to low. The total potassium was found high in an area of 409 ha (24%), moderate in that of 799 ha (46%) and low in that of 513 ha (30%).